Evaluation of Treatment Tolerability, Satisfaction and Laboratory Parameters in HIV+ Patients Switching from Ritonavir Capsule to Tablet Formulation§ - Mtambo, Andy; Harris, Marianne; Toy, Junine; Guillemi, Silvia; Zhang, Wendy; Lima, Viviane. D.; Hogg, Robert; Montaner, Julio S.G.; Hull, Mark (Current HIV Research, 2013)
Background: This study evaluated treatment satisfaction, gastrointestinal tolerability, depressive symptoms and alterations in laboratory parameters before and after switching from ritonavir capsule to tablet formulation. Methods: HIV+ adults switching from ritonavir capsules to tablets were eligible for the study. The HIV Treatment Satisfaction Questionnaire (HIVTSQ), Gastrointestinal Symptom Rating Scale (GSRS) and CES-D Depression inventory were self-administered before, and 3-4 months after switching. Results of laboratory tests within three months of each questionnaire were collected. A subset underwent plasma drug level sampling. Wilcoxon signed rank sum test was used for comparison of continuous variables and McNemar’s test for dichotomised data. Results: Most of the 71 participants were Caucasian men, median age 51 years. Participants were taking ritonavir in combination with either atazanavir (n=48 [67.6%]), darunavir (n=18 [25.4%]), fosamprenavir (n=3 [4.2%]) or saquinavir (n=2 [2.8%]). In general after the switch to tablets, participants reported improved treatment satisfaction (median [interquartile range] HIVTSQ score 53/60 [48, 58] after vs 49/60 [45, 54] before, p <0.001), fewer gastrointestinal symptoms (GSRS score 4/45 [1, 9] vs 5/45 [3,13], p < 0.001) and had higher HDL cholesterol (1.22 mmol/L [1.07, 1.45] vs 1.09 mmol/L [0.90,1.32], p = 0.003) and lower total cholesterol/HDL ratio (3.82 [3.05, 4.40] vs 4.23 [3.45, 4.84], p<0.001). There were no significant changes in plasma viral load, CD4 counts, depression scores, or atazanavir or ritonavir trough levels. Conclusion: Results of this study suggest that the newer tablet formulation of ritonavir is better tolerated and has fewer gastrointestinal side effects than the older capsule formulation.
Keywords: Ritonavir tablet